Fabrication and characterization of lead sulfide (PbS) thin film based heterostructure (FTO/CdS/PbS/Ag) solar cell by nebulizer spray method. (20th February 2019) - Rosario, S Rex; Kulandaisamy, I; Arulanantham, A M S; Deva Arun Kumar, K; Valanarasu, S; Shkir, Mohd; Kathalingam, A; AlFaify, S
Abstract: This work deals with the study on the key properties of PbS thin films prepared by simple nebulizer spray method. The structural study done by XRD exhibited cubic crystal structure with polycrystalline nature for the deposited PbS films. The obtained crystallite size was varied between 41 to 55 nm for various molar concentrations. The morphology study done by SEM displays uniform distribution of the grains all over the surface of the prepared PbS thin films. The observed band gap value was decreased from 1.8 eV to 1.51 eV for various molar concentrations. The emitted PL intensity was strong at about 580 nm which is related to the near band edge (NBE) emission. Electrical studies performed by Hall Effect measurement confirm the p -type conductivity of prepared films. Resistivity and carrier concentrations are 2.92 × 10 3 Ωcm and 4.83 × 10 13 cm −3 respectively for the deposited films. In addition, a heterojunction solar cell of structure FTO/n-CdS/p-PbS/Ag was produced and its conversion efficiency was ∼0.39%. The nebulizer spray technique is very useful and novel method for the preparation of device quality PbS thin film.